Papillary thyroid carcinoma metastatic to the pancreas: Case report. Issue 3 (27th November 2018) - Cho, Margaret; Acosta‐Gonzalez, Gabriel; Brandler, Tamar C.; Basu, Atreyee; Wei, Xiao‐Jun; Simms, Anthony
Abstract : Papillary thyroid carcinoma (PTC) is generally associated with an excellent long‐term outcome. Distant metastasis is rare with only 5‐7% of patients developing distant disease. Metastasis of PTC to the pancreas is an exceedingly rare occurrence. To date, few cases have been reported. We present the case of an 81‐year‐old man with past medical history of PTC status post total thyroidectomy with local recurrence treated with radioactive iodine and selective neck dissection. Ten years after his initial diagnosis, PET‐CT scan revealed a new hypermetabolic 1.1 cm × 0.9 cm left lower lobe lung nodule and hypermetabolism in the proximal body of the pancreas. Follow‐up MRI cholangiogram showed a 1.0 × 0.8 cm T1 hypointense lesion in the proximal body of the pancreas. Endoscopic ultrasound‐guided fine‐needle aspiration biopsy of the pancreatic mass showed neoplastic epithelial cells arranged in papillary clusters with fibrovascular cores and syncytial sheets with high nuclear to cytoplasmic ratio, visible nucleoli, nuclear pallor, focal nuclear grooves, and rare intranuclear pseudoinclusions. Immunohistochemical stains performed on the smears showed positive nuclear expression of TTF‐1 and PAX‐8. The findings were consistent with metastatic PTC. Surgical resection of the lung nodule confirmed metastatic PTC. Pancreatic metastases usually occur after long time intervals with reports of up to 8 years in PTC. This makes the diagnosis more challenging, and metastatic disease should always be in the differential diagnosis in cases presenting with a pancreatic mass, especially in patients with a prior malignancy.